Tutoring: A Method of Facilitating Active Learning - Nurmukhanbetova, Ardagul N.; Abdykhalykova, Zhazira E.; Abdullayeva, Zhazira D.; Baimanova, Ulbossyn Sh.; Sadykova, Aigul K. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: To create one of the possible conditions for student-centred education, the authors’ research group developed a tutoring support programme for adaptation of students to the educational process of the school and implemented it into practice. Background: The necessity of implementing tutoring support in Kazakhstan education is associated with the processes of integration of Kazakhstan into the world educational space, with the introduction of a multi-level educational system, the development of new educational standards such as the Bologna Process. Student-centred education is the fundamental principle of the reform in light of the Bologna process in inclusive education. Tutoring support addresses the needs and meets the requirements of the transition to the individualisation of learning and the variability of educational programmes. Method: The study included the following research methods: theoretical (analysis, synthesis, classification, generalisation, deduction, induction, analogy, and modelling); empirical (observation, survey, questionnaire, and interview); experimental (stating, developmental, and diagnostic experiment); statistical (statistical analysis of the data, qualitative and quantitative analysis of the study results). Results: The results of the pilot programme noted changes in motivational and cognitive activity-target components of adaptation in students of the experimental group who received tutoring support, their academic achievements improved, and their independence in preparation for classes developed. Conclusion: In conclusion, the authors noted that to create conditions for student-centred education, it is necessary to use various kinds of programmes of student academic support in the educational process.